2019
DOI: 10.32604/phyton.2019.06831
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Multi-Tasking Non-Edible Plants for Phytoremediation and Bioenergy Source-A Review

Abstract: Heavy metal contamination of land and freshwater resources is a serious concern worldwide. It adversely affects the health of animals, plants and humans. Therefore, remediation of toxic heavy metals must be highly considered. Unlike other techniques, phytoremediation is a holistic technology and can be used in large scale for soil remediation as it is costless, novel, environmentally-safe and solar-driven technology. Utilization of non-edible plants in phytoremediation is an ingenious technique as they are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 135 publications
(153 reference statements)
0
22
0
4
Order By: Relevance
“…For instance, Tiwari et al [126] reported the current phytoremediation situation in India, where the availability of different phytoremediator trees is abundant, for example, Azadirachta indica, Acacia nilotica, Prosopis juliflora, Terminalia arjuna, Pongamia pinnata, and Eucalyptus tereticornis. Special interest is the use of Azaridachta indica and Acacia nilotica not only for their use in traditional medicine, personal care, and the presence of biologically active compounds [127] but also because of restoration of eroded soils and the phytoremediation potential, removing organic compounds [128,129], radionuclides [130], and toxic metals [122,131,132]. The studies report using seeds of A. indica from phytoremediation to produce ethanol from biomass fermentation and biodiesel via base-catalyzed transesterification.…”
Section: Liquid Biofuelsmentioning
confidence: 99%
“…For instance, Tiwari et al [126] reported the current phytoremediation situation in India, where the availability of different phytoremediator trees is abundant, for example, Azadirachta indica, Acacia nilotica, Prosopis juliflora, Terminalia arjuna, Pongamia pinnata, and Eucalyptus tereticornis. Special interest is the use of Azaridachta indica and Acacia nilotica not only for their use in traditional medicine, personal care, and the presence of biologically active compounds [127] but also because of restoration of eroded soils and the phytoremediation potential, removing organic compounds [128,129], radionuclides [130], and toxic metals [122,131,132]. The studies report using seeds of A. indica from phytoremediation to produce ethanol from biomass fermentation and biodiesel via base-catalyzed transesterification.…”
Section: Liquid Biofuelsmentioning
confidence: 99%
“…The translocation of heavy metals is important to understand as they can concentrate into edible products made from the plant (Abdelsalam et al, 2019). Most of the heavy metals are accumulated into the roots (Ahmad et al, 2014;Citterio et al, 2003;Giovanardi et al, 2002;Shi et al, 2011;, though Cd and Zn are accumulated mostly into the shoots (Löser et al, 2002) or more specifically into the leaves (Arru et al, 2004;Eboh and Thomas, 2005;Giovanardi et al, 2002;Linger et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The proper management of tailings can prevent or mitigate the risks in the functioning of ecosystems and human health originating from heavy metal contaminations [5][6][7]20]. Phytomanagement is cost effective and environmentally friendly technique suitable for decreasing the environmental risks from metal(loid) enriched mine tailings [6,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Phytomanagement is cost effective and environmentally friendly technique suitable for decreasing the environmental risks from metal(loid) enriched mine tailings [6,21,22]. Several plants plants are used for the phytomanagement, as these show several edaphic constrains interferring with plant growth including heavy metal toxicity [20,23,24]. Native plant species are preferred because these are adapted not only to the contamination of tailings but also to the local climatic conditions [5,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation